Thermal activation energy of 3D vortex matter in NaFe(1−x)Co(x)As (x = 0.01, 0.03 and 0.07) single crystals - Choi, W. J. (Sci Rep, 2017)
We report on the thermally activated flux flow dependency on the doping dependent mixed state in NaFe(1−x)Co(x)As (x = 0.01, 0.03, and 0.07) crystals using the magnetoresistivity in the case of B//c-axis and B//ab-plane. It was found clearly that irrespective of the doping ratio, magnetoresistivity showed a distinct tail just above the T (c,offset) associated with the thermally activated flux flow (TAFF) in our crystals. Furthermore, in TAFF region the temperature dependence of the activation energy follows the relation [Formula: see text] with q = 1.5 in all studied crystals. The magnetic field dependence of the activation energy follows a power law of [Formula: see text] where the exponent α is changed from a low value to a high value at a crossover field of B = ∼2 T, indicating the transition from collective to plastic pinning in the crystals. Finally, it is suggested that the 3D vortex phase is the dominant phase in the low temperature region as compared to the TAFF region in our series samples.